The Effect of Green Involvement on Corporate Sustainability Performance with Employee Performance as an Intervening Variable At PT. Angkasa Pura Indonesia Pekanbaru Branch Office - Dian Puspita Novrianti; Rizqi Ramadhan; Kurniawaty Fitri (Westscience Press, 2025)
This study aims to analyze the effect of Green Involvement on Corporate Sustainability Performance with Employee Performance as an intervening variable at PT. Angkasa Pura Indonesia, Pekanbaru Branch Office. This research employs a quantitative approach using a survey method by distributing questionnaires to 117 respondents who are employees of PT. Angkasa Pura Indonesia, Pekanbaru Branch Office. The data collection techniques used in this study were questionnaires, interviews, and observations, which were analyzed using instrument testing, descriptive statistics, classical assumption tests, Sobel test, and hypothesis testing. The results indicate that Green Involvement has a positive and significant effect on Employee Performance, Green Involvement also has a positive and significant effect on Corporate Sustainability Performance, and Employee Performance positively and significantly affects Corporate Sustainability Performance. Furthermore, Employee Performance mediates the relationship between Green Involvement and Corporate Sustainability Performance. These findings imply that employees’ green involvement not only directly influences corporate sustainability but also indirectly through improved employee performance. This study highlights that implementing Green Human Resource Management (Green HRM) practices is an essential strategy for companies to enhance sustainability performance and achieve long-term competitiveness.